2001
DOI: 10.1074/jbc.m108523200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tyrosine Phosphorylation in Ligand-independent Sequestration of CXCR4 in Human Primary Monocytes-Macrophages

Abstract: The chemokine stromal cell-derived factor (SDF)-1 and its receptor, CXCR4, play important roles in human immunodeficiency virus type 1 (HIV-1) pathophysiology, leukocyte trafficking, inflammation, hematopoiesis, embryogenesis, angiogenesis, and cancer metastasis. The effects of cytokines on the regulation of CXCR4 function were investigated in human primary monocytes-macrophages. The expression of functional CXCR4 on the cell surface was demonstrated by the detection of ligandinduced Ca 2؉ mobilization, chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 68 publications
4
64
0
1
Order By: Relevance
“…But there are also exceptions, such as granulocyte-macrophage colony-stimulating factor increased the abundance of GRK3 and might contribute to the sequestration of CXCR4 in human primary monocytederived macrophages (31). The similar result was found in our experiments, as pan-GRK inhibitor (heparin) also prevented the CCR9 internalization triggered by IL-2 and IL-4 together.…”
Section: Discussionsupporting
confidence: 89%
“…But there are also exceptions, such as granulocyte-macrophage colony-stimulating factor increased the abundance of GRK3 and might contribute to the sequestration of CXCR4 in human primary monocytederived macrophages (31). The similar result was found in our experiments, as pan-GRK inhibitor (heparin) also prevented the CCR9 internalization triggered by IL-2 and IL-4 together.…”
Section: Discussionsupporting
confidence: 89%
“…For example, rapid internalization of CXCR4 was observed after stimulation of lymphocytes with phorbol esters [14,26]. Interestingly, for monocytes Wang et al reported a down-modulation of CXCR4 from the cell surface after overnight stimulation with GM-CSF, while lymphocytes were not affected [27]. Cytokine-induced down-regulation of CXCR4 from the cell surface of monocytes was mediated through an endocytotic mechanism in the absence of protein degradation, similar to our observations for cytokine-induced internalization of CXCR4 on neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…However, this model using KO mice must consider the fact that these animals may be compromised in the ability of monocytes to traYc to SG, the primary means by which virus seeds this organ. Indeed, IL-10 modulates expression of chemokine receptors on at least human monocytes, with reports of IL-10 mediated upregulation of CCR2, CCR5, and CXCR4 [14,16,47,56,60]. It is possible therefore that in the absence of IL-10, less virus entered the SG, as opposed or in addition to more rapid and eYcient viral clearance.…”
Section: Il-10 As a Potential Inhibitor Of Antiviral Activity In Salimentioning
confidence: 99%